Epoxidation of Palm Kernel Oil Fatty Acids - Fong, Michelle Ni Fong; Salimon, Jumat (Journal of Science and Technology, 2012)
Epoxidation of palm kernel oil fatty acids using formic acid and hydrogen peroxide was carried out effectively using a homogeneous reaction. It was found that epoxidation reaction occurred optimally at a temperature of 40oC and reaction time of 120 minits. The oxirane conversion was the highest at 1.46mol and 0.85mol of hydrogen peroxide and formic acid respectively. It was found that a maximum of 99% relative conversion of ethylenic oxirane was obtained, similar to the conversion of iodine value. The formation of epoxide adduct of palm kernel oil fatty acids (FAPKO) was confirmed by 1H NMR and 13C NMR spectral analysis showed the disappearance of double bonds and replaced by epoxy group in the EFAPKO.